2008
DOI: 10.1016/j.pec.2008.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Entertainment education for prostate cancer screening: A randomized trial among primary care patients with low health literacy

Abstract: Objective-To evaluate an entertainment-based patient decision aid for prostate cancer screening among patients with low or high health literacy.Methods-Male primary care patients from two clinical sites, one characterized as serving patients with low health literacy (n=149) and the second as serving patients with high health literacy (n=301), were randomized to receive an entertainment-based decision aid for prostate cancer screening or an audiobooklet-control aid with the same learner content but without the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
154
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(160 citation statements)
references
References 23 publications
(30 reference statements)
5
154
1
Order By: Relevance
“…In other randomized controlled trials that included a web-based decision aid for PCa screening, participant knowledge consistently improved [21][22][23][24][25][26][27][28], while decisional conflict results were more variable, with some studies reporting a decrease compared to Implications Practice: Clinicians should encourage the use of web-based decision aids to help patients become aware of the facts associated with medical tests and treatments and to aid informed decision making.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In other randomized controlled trials that included a web-based decision aid for PCa screening, participant knowledge consistently improved [21][22][23][24][25][26][27][28], while decisional conflict results were more variable, with some studies reporting a decrease compared to Implications Practice: Clinicians should encourage the use of web-based decision aids to help patients become aware of the facts associated with medical tests and treatments and to aid informed decision making.…”
Section: Introductionmentioning
confidence: 96%
“…Tracking software captured website use, allowing for an investigation of whether use of informational sections, testimonial videos, and the values clarification tool were associated with decisional outcomes. Based on prior studies in several domains [14,28,[31][32][33][34] and on a model of Internet interventions [14], we hypothesized that greater interaction with the website would be associated with improved knowledge and satisfaction, decreased decisional conflict, and decreased screening rates.…”
Section: Introductionmentioning
confidence: 99%
“…While participants in the print arm reported that the decision aid was a better length than participants in the web arm, we found few differences between the print and web arms. 15 For example, men in each arm had a similar response to the patient-physician communication outcomes and to the decision aid content, with few people reporting difficulty understanding the information and most reporting that the decision aids were very or extremely helpful. In multivariable, adjusted analyses, men were equally likely to understand that the overall message of the decision aid was neutral with regard to screening.…”
Section: Discussionmentioning
confidence: 99%
“…Another study limitation was the overall participation rate of 39.5 %. However, this rate is typical of decision aid studies that enrolled participants by mail and telephone as opposed to in conjunction with an office visit, 11,15 and has the advantage of yielding a sample that is potentially more generalizable, as participants had fewer eligibility restrictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation